The Impact of COVID-19 Pandemic in Nepali Enterprises - Silwal, Prem Prasad (The Spectrum, 2023)
The purpose of this study is to assess the scenario of Covid-19 outbreak in Nepali firms and suggest policy-related issues for the survival and growth of small medium enterprises in Nepal. To carry out this research, the firms were identified based on the list published by the business directory, and a total of 500 questionnaires were distributed to these businesses, 404 responses were received. Responses, analyzed under descriptive research design, show that the majority of the small medium enterprises are highly affected by the pandemic and they have faced several difficulties such as decrease in demand, loss of profit, financial problem, etc. The analysis also shows that the number of business activities have been limited, and small and medium-sized businesses, in particular, are at high risk. The paper recommends the government should announce a special plan for businesses in order for them to survive the pandemic and return to normalcy gradually. The evidence shows that in this difficult situation, a company's internal profits can be low and bankers may be reluctant to lend money. As such, the company should actively consider using cash from existing investors.